Essences, Identities and Individuals - (:unkn) unknown (My University, 2025)
Consider an individual – for instance, yourself. Major philosophical issues among which individuation and the ontology of individuals face metaphysicians with such questions as: what makes it the case that you are you, and you are different from every other individual – e.g., from me? What condition, or what collection of conditions, is both necessary and sufficient for being identical with you, hence different from any other individual? This project deals with Haecceitism, a view according to which the identity of individuals is primitive, both intra- and transworldly. According to a haecceitist, given an individual x, it is possible that no collection of purely qualitative conditions is both necessary and jointly sufficient for being identical with x. However, this is not yet a definition: the notion of qualitative needs to be characterized first. In fact, the debate about Haecceitism in analytic metaphysics, started by Robert Adams and David Kaplan some decades ago, has not expired yet, and a great part of it still consists in attempts to properly define the very doctrine at issue. Our project will prove innovative in several ways. It will address the lack of a clear-cut definition of the notion of 'individual' in the debate about Haecceitism – a problem that seems to have been ignored so far. The definition of 'qualitative' that haecceitists usually assume critically depend on that notion; by bridging such a gap, we will help reaching a proper understanding of Haecceitism. In the latter concern, we will advance a proposal that was never explicitly defended before: we will suggest that Haecceitism can adequately be characterized as the claim that it is not the case that, necessarily, individuals have qualitative individual essences. So construed, the view has interesting consequences on any account of essentialism and modality de re. This project will also help solving a problem that earlier conceptions have left open: the question whether a Kripkean approach to modal talk entails Haecceitism. Finally, notions of ontological dependence and of identity-dependence in particular will play a main role in our work; this will open the way to dialogue with current research about fundamentality and grounding. The project group will consist of a senior researcher, Fabrice Correia (professeur extraordinaire, University of Neuchâtel) and a doctoral collaborator, Maria Scarpati (assistante-doctorante, University of Neuchâtel).
Keywords: Metaphysics; J. Duns Scotus; Ontology; Ontological dependence; Individuals; R.M. Adams; Identity; Identity-dependence; Modality; Transworld identity; Essence; Thisness; Direct reference; D. Kaplan; Properties; Haecceitism; Essentialism; Proper names; Bare identities; Leibniz's law; Haecceitas; S. Kripke; Individuation; Primitiveness; Possible worlds